OUR EXPERIENCE IN INTRODUCTION OF COMBINATION MIFEPRISTON / MISOPROSTOL FOR FIRST TRIMESTER MEDICAL ABORTION ON UNIVERSITY CLINIC FOR GYNECOLOGY AND OBSTETRICS IN SKOPJE, REPUBLIC OF NORTH MACEDONIA: Georgievska Jadranka1, Tofoski Gligor1, Daneva Ana1, Jovanovska Viktorija1, Sozovska Eva1, Dimitrovski Sašo1, Buklioska Adriana1, Nikolovska Katerina 1 1University clinic for gynecology and obstetrics in Skopje, University „Ss Cyrilus and Methodius“, Medical faculty Skopje, Republic of North Macedonia - Georgievska, Jadranka Dimitar (Medicinski časopis, 2022)
Introduction: Medical abortion according to recommendation of the World Health Organization (WHO) is safe and effective method for termination of pregnancy. Aim: To evaluate satisfaction of patients after introduction of first trimester medical abortion and effectivines of method. Materials and methods: In retrospective analysis experiences with introduction of first trimester medical abortion on University Clinic for gynecology and obstetrics in Skopje, R.N.Macedonia in period from 01.10.2020 to 01.10.2021 are presented. Tablets Mifepristone and Misoprostol were used with treatment regimen adapted with protocols of the WHO. Results: During the period of one year 189 patients were treated with combination Mifepristone/Misoprostol for first trimester abortion. Instrumental revision of the cavum of womb was made in 11 patients (5,8%). Medical abortion was repeated in 5 patients (2,6%). Satisfied with the method were 92% of the patients. Eficacy of the method was 95%. Very little complication were recorded (proloned vaginal bleeding, diarrhoea, vomiting etc.). Conclusions: First trimester medical abortion is safe, effective method especially useful during the pandemy with Corona virus, because can be applied without hospitalization in home atmosphere, with consultation with gynecologist. Key words: medical abortion, mifepriston, misoprostol